Beatspeak communicating pakisama in the fourth estate - Ordinario, Marie Carisa U.
This master's thesis examines group dynamics in four beats - Bangko Sentral ng Pilipinas and Department of Fiannce; House of Representatives; Malacañang; and Telecommunication and Transportation. Using Sikolohiyang Pilipino, particularly Jocano's framework on samahan and Hyme's Ethnography of Communication, the study discovers the ways, processes and speech codes that Filipino journalists use and which demonstrate pakikisama in communicating in the beat as it explores the reasons journalists employ pakikisama in their communication interactions in the news beat. The thesis uncover the ways by which Filipino culture is expressed in the beat and how it affects beat dynamics. Through 40 Key Informant Interviews (KIIs), four case studies, and participants observation, the study surfaces the norms, forms, and cultural codes used by reporters to conform to and resist against practices in the beat; the reasons journalists choose to use pakikisama in the beat such as avoiding being outscooped, lightening one's workload, fostering belongingness, and avoiding hurting feelings of others. This research also finds that Filipino culture is expressed in journalism through Journalistic Compadrazgo, Beat Fiesta, and the Journalist as Kapwa. The study also has theoretical, methodological, and practical implications on beat dynamics, journalism mentoring, and newspaper management.